A sustainable polymer and coating system based on renewable raw materials. Issue 24 (2nd December 2022) - Hermens, Johannes G. H.; Freese, Thomas; Alachouzos, Georgios; Lepage, Mathieu L.; van den Berg, Keimpe J.; Elders, Niels; Feringa, Ben L.
Abstract : A complete biobased process towards polymers and coatings using starting materials derived from renewable resources and implementing sustainable synthetic steps. Abstract : Paints and coatings are widely used in modern society and their current production is mainly dependent on the petrochemical industry. The establishment of processes using sustainable alternative monomers based on biorenewable resources, using exclusively biobased reagents and green synthetic transformations are highly warranted for a more sustainable future. Herein, we report on a sustainable polymer and coating system based on the monomer methoxybutenolide, a biobased acrylate alternative. Methoxybutenolide and the comonomer dodecyl vinyl ether are synthesized from biobased platform chemicals using the environmentally benign synthetic transformations photooxygenation and vinylation. For the photooxygenation, a biobased photosensitizer was developed showing high quantum yields. The monomers were copolymerized using biomass derived (photo)initiators to yield fully biobased polymers and coatings with properties comparable to acrylate based coatings.